APPLICATION OF SEISMIC INTERPRETATION AND VISUALIZATION FOR STRATIGRAPHIC EXPLORATION POTENTIAL IN B FIELD, MALAY BASIN - JALUDIN, JAMAL EMIR (2020)
The previous exploration works conducted in 1991 focused on structural trap of low relief anticline bounded by northeast-to-southwest fault. The volume of hydrocarbon estimated is only about 8.1 Billion Standard Cubic Feet (BSCF) and thus deemed as not profitable to produce. This research study is conducted to assess the potential of stratigraphy trap of fluvial channel in group F through integration of well, seismic, and geological information of the field. It is commonly known that exploration of stratigraphic trap is always associated with high risk because the trap needs to be laterally and vertically sealed to trap hydrocarbon accumulation. The availability of 3-D seismic data along with computing resources and advance interpretation workflows have made it possible to address and minimize the risk. The results of facies modelling with integration of geological information manage to delineate the distribution of transgressive shale as the sealing lithology potential for gas-filled sand within the stratigraphic trap. The integration in between results is utilized to reduce uncertainty and increase the reliability of results.